PWE-090 Does my patient–s normal liver biopsy mean they won't develop liver disease?. (22nd June 2015) - Hudson, B; Thiagarajan, P; Ramappa, V; Kaye, P; Aithal, G
Abstract : Introduction: Liver biopsy remains a commonly used investigation amongst patients with abnormal liver biochemistry and normal serology, both in the diagnosis and staging of liver disease. Although commonly considered the "gold standard" it typically samples approximately 1/50, 000 th of the total liver mass and as such diffuse liver disease could plausibly be missed. 1 It is associated with complications of pain and bleeding and has a small but appreciable mortality (0.01–0.17%). 2 We report follow up data from a Nottinghamshire cohort of patients with abnormal liver biochemistry and normally reported liver biopsy between 1992–2001. We aim to assess whether a normal liver biopsy in the context of abnormal liver biochemistry is protective against development of and death from chronic liver disease. Method: Patients with a normally reported liver biopsy and abnormal liver chemistry from Nottingham University Hospitals between 1992–2001 were identified from retrospective scrutiny of local Histopathology databases. Patient notes and computer records as of 1 st January 2015 were analysed to assess mortality, cause of death (where applicable), and development of cirrhosis. Office of National Statistics (ONS) UK population data was used to provide a comparable "control" group. Results: 171 patients were identified. 32 (18.7%) were known to have died by 1 st Jan 2015. Of those who had died, 2 (6.5%) had hepatocellular carcinoma secondary to cirrhosis recorded as cause of death. This figure is significantly higher than the 1.53% of deaths attributed to liver disease in the UK population in 2010. 3 We intend to report on the incidence of cirrhosis in the remainder of the cohort as compared to a matched control population. Conclusion: Our data suggest that a normal liver biopsy in the presence of abnormal liver biochemistry does not protect against future death from complications of chronic liver disease. We question whether alternative non-invasive markers of fibrosis could potentially have comparable or superior value in predicting development of cirrhosis and death from liver disease in this patient group. Disclosure of interest: None Declared. References: Guido M, Rugge M. Liver biopsy sampling in chronic viral hepatitis. Semin Liver Dis . 2004;24(1):89–97 Grant A, Neuberger J. Guidelines on the use of liver biopsy in clinical practice. BSG . See comment in PubMed Commons below Gut . 1999;45 (Suppl 4):IV1–IV11 Office of National Statistics – Mortality statistics – England and Wales, 2010